Anatomical changes of the CNS in the course of schizophrenia and recurrent depression a review of current knowledge - Gmyz, Joanna; Zubrzycka, Weronika; Grzech, Patrycja; Kreczyńska, Lena (Journal of Education, Health and Sport, 2025)
Introduction and purpose of the study: Schizophrenia and recurrent depressive disorder are important mental disorders worthy of special interest in both the fields of psychiatry and neuroradiology. The studies presented in the following paper have made it possible to see a correlation between specific symptoms specific to the aforementioned disease entities and the location of pathological changes within the CNS. Review methods: The article was based on a review of scientific papers available in the PubMed electronic database, in order to select the appropriate quality of scientific articles, appropriately selected keywords were used: “schizophrenia”, “recurrent depressive disorder”, “neuroimaging”. Description of the state of the art: Anatomical changes within the CNS are associated with various factors, such as genetics, environment or neurochemical interactions, which affect the development and course of the mental disorders in question. Neuroimaging techniques such as computed tomography (CT) and magnetic resonance imaging (MRI) allow us to detect pathologies in specific areas of the brain and correlate them with the clinical condition of the subject. In this way, we are constantly expanding our knowledge of the connections and neuronal loops that determine proper human functioning in society. Summary: The diseases presented not only affect the functioning of the patient himself, but also affect his loved ones and the health care system. With the ability to observe the brains of patients with schizophrenia and recurrent depression, knowledge of its structure has expanded significantly. This is a key element in developing more targeted and effective therapies, both pharmacological and psychotherapeutic.